Immersing Japanese students into English language learning: Songs, games and cultures - Syafryadin Syafryadin; Saad Boulahnane (Jurnal Cakrawala Pendidikan, 2021)
Learning English for Japanese is not as easy as people think. Teachers should provide a way to immerse Japanese students. Therefore, this study aimed to understand how Japanese English teachers immersed students in learning English, what challenges that students and teachers were facing and their perceptions toward the International Work Camp. This case study collected the data from 20 students and 10 teachers from various countries using interviews and an observation checklist. The data were analyzed in several steps, starting from data collection, data reduction, data display to data conclusion. The findings of this study show that Japanese and non-Japanese teachers collaborated to immerse students in attractive teaching ways, such as drilling techniques, gaming, singing, using cards, playing outside, grouping, etc. Besides, teachers also kept motivating and reinforcing them to speak English. Furthermore, students’ barriers in speaking were pronunciation, anxiety, grammar, vocabulary, and less practice. Problems were not only faced by students as teachers also had hindrances. Therefore, through the International Work Camp, students could learn to speak English effectively. They could interact with other students and get English speaking competence immersion with several native English teachers. The students also had good perceptions of this work camp.